Annexin A1 peptide is able to induce an anti-parasitic effect in human placental explants infected by Toxoplasma gondii. (October 2018) - de Oliveira Cardoso, Marystela Fávero; Moreli, Jusciele Brogin; Gomes, Angélica Oliveira; de Freitas Zanon, Caroline; Silva, Ana Elizabete; Paulesu, Luana Ricci; Ietta, Francesca; Mineo, José Roberto; Ferro, Eloísa Amália; Oliani, Sonia Maria
Abstract: This study was conducted to investigate annexin A1 (ANXA1) functions in human placental explants infected with Toxoplasma gondii (T. gondii) . We examined the first and third trimester placental explants infected with T. gondii (n = 7 placentas/group) to identify the number and location of parasites, ANXA1 protein, potential involvement of formyl peptide receptors (FPR1 and FPR2), and COX-2 expressions by immunohistochemistry. Treatments with Ac2-26 mimetic peptide of ANXA1 were performed to verify the parasitism rate (β-galactosidase assay), prostaglandin E2 levels (ELISA assay), and ANXA1, FPR1 and COX-2 expression in third trimester placentas. Placental explants of third trimester expressed less ANXA1 and were more permissive to T. gondii infection than first trimester placentas that expressed more ANXA1. Ac2-26 treatment increases endogenous ANXA1 and decreases parasitism rate, COX-2, and prostaglandin E2 levels. Altogether, these data provide further insight into the anti-parasitic and anti-inflammatory effects of ANXA1 in placentas infected with T. gondii . Graphical abstract: Highlights: Gestational age of placenta sample modulate the distribution and number of T. gondii . Ac2-26 peptide treatment is able to reduce parasitism rate in placental explants of third trimester of pregnancy. ANXA1, FPR1 and COX-2 are differentially expressed in infected trophoblast cells of first and third trimester of gestation.